PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI BPJS KESEHATAN KANTOR CABANG LUBUK LINGGAU - Ervina; Dedi Hartawan; Fretty Welta (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2022)
The purpose of the research is to find out the effect of Work Environment and Individual Characteristics on Performance of employees of BPJS Kesehatan Branch of Lubuklinggau. The population of this research is all 44 employees who worked at BPJS Kesehatan Branch of Lubuklinggau. Who were used also as the respondents. The data of this research were collected through questionnaires, observation and literature research. The method of data analysis in this research is survey research with quantitative method. The analytical tool of this study is multiple linear regression analysis with F Test and t test to test the research hypothesis. The results showed that partially the work environment significantly influence the performance of employees of BPJS Kesehatan Branch of Lubuklinggau. Partially Individual Characteristics have a significant effect on the performance of employees of BPJS Kesehatan Branch of Lubuklinggau employees. Simultaneously the work environment and individual characteristics significantly influence the performance of the of employees of BPJS Kesehatan Branch of Lubuklinggau.